Linux device drivers. - Rubini, Alessandro, ....-; Corbet, Jonathan, ....- (Beijing : O'Reilly, 2001)
1. An introduction to device drivers 2. Building and running modules 3. Char drivers 4. Debugging techniques 5. Enhanced char driver operations 6. Flow of time 7. Getting hold of memory 8. Hardware management 9. Interrupt handling 10. Judicious use of data types 11. Kmod and advanced modularization 12. Loading block drivers 13. MMAP and DMA 14. Network drivers 15. Overview of peripheral buses 16. Physical layout of the kernel source
Keywords: Linux (operating system).; Operating systems